Efficiency of core-level interatomic Coulombic decay in rare-gas dimers - Liu, Liping; Kolorenč, Přemysl; Gokhberg, Kirill (Physical review, 2020)
In this work we investigated the competition between the local Auger decay and core-level interatomic Coulombic decay (ICD) processes in core ionized rare-gas dimers. We computed the respective partial decay widths for the 4d vacancy in Xe2, XeKr, and XeAr, as well as for the 3d vacancy in Kr2. We found that the efficiency of ICD is strongly increased with decreasing interatomic distance and decreasing energy transfer in the decay step. The ICD-to-Auger ratio in the Franck-Condon region, where the decay occurs, is at most 0.26%. However, it reaches a few percentage points in larger clusters and becomes amenable for experimental observation. The small value of the branching ratio is due to large interatomic distances in the dimers (4-4.4 Å). Our results also indicate, in accordance with previous measurements, that in hydrogen-bonded and microsolvated clusters, where the distances between the monomers are 2-3 Å, core-level ICD should become an important pathway for charge redistribution following the absorption of hard x-rays.
Gesehen am 09.04.2020